2003
DOI: 10.1038/sj.bjc.6601225
|View full text |Cite
|
Sign up to set email alerts
|

CD40-targeted adenoviral GM-CSF gene transfer enhances and prolongs the maturation of human CML-derived dendritic cells upon cytokine deprivation

Abstract: Vaccination with autologous leukaemia-derived dendritic cells (DC) presents an adjuvant treatment option for chronic myeloid leukaemia (CML). Here, we show that high-efficiency CD40-targeted adenoviral gene transfer of GM-CSF to CML-derived DC induces long-lived maturation in the absence of exogenous cytokines and may thus ensure protracted stimulation of CML-specific T cells upon vaccination. It has become clear from clinical observations that chronic myeloid leukaemia (CML) is amenable to T-cell-mediated imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In agreement with these results, previous reports have demonstrated that Ad vectors expressing GM-CSF induced maturation of DC and that this effect was associated with NF-kB activation. 6,33,34 In order to establish that the generation of tumorspecific immune response was responsible for the observed antitumor effect, we carried out IFN-g ELISPOT assay. We observed that YKL-GB induced significantly higher immune cell activation than YKL-1.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these results, previous reports have demonstrated that Ad vectors expressing GM-CSF induced maturation of DC and that this effect was associated with NF-kB activation. 6,33,34 In order to establish that the generation of tumorspecific immune response was responsible for the observed antitumor effect, we carried out IFN-g ELISPOT assay. We observed that YKL-GB induced significantly higher immune cell activation than YKL-1.…”
Section: Discussionmentioning
confidence: 99%
“…In CML 69,70 and AML, [71][72][73] dendritic cells can be generated from ex-vivo leukemia blasts themselves, which has the added advantage of negating the need to load tumor-associated antigen, while expressing these antigens in the context of the necessary co-stimulatory signals. Leukemia blast derived cell lines 74 that have been stimulated to differentiate into dendritic like cells with antigen presenting capabilities.…”
Section: Leukemia Derived Dendritic Cellsmentioning
confidence: 99%
“…Delivery of genetic material encoding the tumor antigen instead of the antigen itself would sustain the presentation of the antigens by DCs for longer period of time. Several studies by Curiel et al, have used an adenoviral vector to deliver genes encoding target antigens to the DCs [78,[92][93][94][95][96][97][98][99].…”
Section: 5mentioning
confidence: 99%